The world that fear made : slave revolts and conspiracy scares in early America - Sharples, Jason T., 1981- (Early American studies., 2020)
"The conspiracy scare phenomenon emerged from a combination of enslaved people's traumatic experience of terror and enslavers' awareness of their culpability and exposure to the people whom they exploited. On at least ninety-six documented occasions before 1790, colonial officials in eastern North America and the British Caribbean believed that they discovered evidence of a "slave conspiracy"--A detailed plan for insurrection coordinated by a network of enslaved men--just in time to avert the uprising. Often they ended up convincing themselves that they regularly dodged ambushes at decoy fires and averted a world turned upside down. Two questions about conspiracy scares motivate The World That Fear Made. How and why did white colonists, with the coerced involvement of enslaved people, create these particular fears and come to believe in them? And how did people remake their societies in relation to fear and navigate the world that it conjured?"--